Efficient Testing of Wireless Devices from 800 MHz to 18 GHz - Foged, Lars Jacob; Scannavini, Alessandro (Společnost pro radioelektronické inženýrství, 2009)
Small antennas and other modern communication applications are using increasingly higher frequencies while demanding shorter development time and very rapid testing cycles. A fast and accurate way to exhaustively determine antenna performance and/or investigate device malfunction is based on spherical near field measurement techniques combined with probe array technology. This paper describes the innovative design aspects of the StarLab portable antenna measurement system and present results from the validation campaigns including both passive and active measurements. The use of integrated diagnostic and analysis software modules for efficient antenna design and testing is also presented.
Keywords: Antenna Measurements; Spherical Near Field; Probe Array; Small Antennas; OTA (over-the-air) measurements; TRP (Total Radiated Power); TIS (Total Radiated Sensitivity); CTIA (Cellular Telecommunications and Internet Association); 3GPP (3G Partner Part